Surgical treatment of cavernous sinus meningioma with petrous bone invasion causing internal auditory canal stenosis and hearing impairment 7 years after gamma-knife radiosurgery - Yasuhiro Mukai; Takashi Sugawara; Yukika Arai; Taketoshi Maehara (Egyptian Journal of Neurosurgery, 2024)
Abstract Background Surgical intervention for cavernous sinus meningiomas remains challenging because of their anatomically complicated location. We report a case of a cavernous sinus meningioma that enlarged and caused hearing impairment due to internal auditory canal stenosis 7 years after gamma-knife radiosurgery. Case description A 38-year-old man with abducent nerve paralysis and dysesthesia on the left side of the face was diagnosed with a cavernous sinus meningioma with thickened petrous bone. After a year, the patient had mild left-sided hearing impairment, and gamma-knife radiosurgery was performed. At the age of 46, the left hearing impairment worsened, the tumor was slightly enlarged, and petrous bone thickening in the internal auditory meatus had progressed. We partially resected the tumor, which seemed to be viable, and removed the thickened petrosal bone and opened the internal auditory meatus. The tumor was pathologically diagnosed as meningothelial meningioma. The patient’s hearing impairment did not progress, and the residual tumor had not grown for four years. Conclusions Removal of the viable tumor that progressed after gamma-knife radiosurgery and opening of the internal auditory meatus were effective in stopping the worsening of hearing impairment and controlling the tumor.